Brain metastases following radical surgical treatment of non-small cell lung cancer: is preoperative brain imaging important? - O'Dowd, Emma L.; Kumaran, Maruti; Anwar,, Sadia; Palomo, Begoña; Baldwin, David R. (Elsevier, 2014)
Objectives: There is a lack of good quality evidence or a clear consensus of opinion internationally regarding who should receive preoperative imaging of the brain prior to radical treatment for non-small cell lung cancer (NSCLC). We aimed to establish the proportion of patients who developed brain metastases following curative surgery and to estimate how many could have been detected by preoperative magnetic resonance imaging (MR).